Penguatan dan Bimbingan Trend Fashion Islami Bagi Mahasiswi di Universitas Islam Negeri (UIN) Raden Mas Said Surakarta - Fatwa, Dian Islamiati; Zidatin Nurkumala, Emilda Triana (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Capitalism doesn't just impact women but also men. It has even conquered religion and commodified religious symbols. It can infiltrate religious symbols and transform them from within while offering the concept of